1988
DOI: 10.1103/physrevb.37.2502
|View full text |Cite
|
Sign up to set email alerts
|

Diamagnetic susceptibility of a dense electron gas

Abstract: %'e calculate the diamagnetic susceptibility of a uniform interacting electron gas in the random-phase approximation.From this the exact high-density expansion of the diamagnetic susceptibility is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 8 publications
0
98
0
Order By: Relevance
“…Most of these use the Vignale-RasoltGeldart ͑VRG͒ XC functional. 90,91 While current-density effects are expected to be small, it is not clear in what cases the current is actually negligible. For example, Handy and co-workers 89 found that, for HF and H 2 O, the effect of including current-dependent terms in the determination of magnetizabilities was of the order of 0.2ϫ 10 −30 J T −2 .…”
Section: Constrained Search Resultsmentioning
confidence: 99%
“…Most of these use the Vignale-RasoltGeldart ͑VRG͒ XC functional. 90,91 While current-density effects are expected to be small, it is not clear in what cases the current is actually negligible. For example, Handy and co-workers 89 found that, for HF and H 2 O, the effect of including current-dependent terms in the determination of magnetizabilities was of the order of 0.2ϫ 10 −30 J T −2 .…”
Section: Constrained Search Resultsmentioning
confidence: 99%
“…In early papers on both CDFT 7,8 and DFT for superconductors 10 one finds the statement that the chosen densities uniquely determine the corresponding potentials. As we have shown here, these statements are not accurate, and all that is determined uniquely is the ground-state wave function.…”
Section: ͑16͒mentioning
confidence: 99%
“…The appropriate formulation of ͑nonrelativistic͒ DFT is CDFT, 7,8 which is based on the many-body Hamiltonian ͑in atomic units, i.e., បϭeϭmϭ1)…”
mentioning
confidence: 99%
“…Many attempts to develop the approximate form have been presented so far. 8,9,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] We have already suggested two strategies for treating the approximate form. 22 One is to start with the coupling-constant expression of the exchangecorrelation energy functional of the CDFT.…”
Section: Introductionmentioning
confidence: 99%